The INTEGRAL CALCULUS MODULE THROUGH MOBILE LEARNING IN MATHEMATICS LEARNING: THE INTEGRAL CALCULUS MODULE THROUGH MOBILE LEARNING IN MATHEMATICS LEARNING - Endang Istikomah; Sari Herlina (Mathematics Research and Education Journal, 2020)
. The purpose of this research is to give information to educators and students that the use of modules accompanied by IT can make learning more effective. Furthemore, the purpose of using the integral calculus module through mobile learning is to be able to change the way students learn, make it easier for students to understand integral concepts, be able to study anywhere and without lecturers, change the smartphone function from just playing social media to learning. This type of research is a qualitative descriptive study through in-depth observation and interviews. The mathematics module is a reference that can facilitate students in learning. Integral calculus for one of the courses that require modules to make learning easier and more enjoyable. Moreover, the module is juxtaposed with mobile learning. Modules are designed by lecturers who teach based on their experience while teaching, so that the language, content, sentence modules that are paired by mobile learning are more favored by students and can follow the speed of their mathematics learning. Therefore, educators can use modules and mobile learning applications in learning mathematics.